©100 points© ☺☺
Prove that both the roots of the equation
( x - a ) ( x - b ) + ( x - b ) ( x - c ) + ( x - c ) ( x - a ) = 0 .
are real but they are equal only when a = b = c .
No spam!!!
Answers
▶ Question:-
→ Prove that both the roots of the equation
( x - a ) ( x - b ) + ( x - b ) ( x - c ) + ( x - c ) ( x - a ) = 0 .
are real but they are equal only when a = b = c .
We have,
°•° ( x - a ) ( x - b ) + ( x - b ) ( x - c ) + ( x - c ) ( x - a ) = 0 .
⟹ x² - bx - ax + ab + x² - cx - bx + bc + x² - ax - cx + ac = 0 .
⟹ 3x² - 2bx - 2ax - 2cx + ab + bc + ca = 0 .
⟹ 3x² - 2x( a + b + c ) + ( ab + bc + ca ) = 0 .
When equation is compared with Ax² + Bx + C = 0 .
Then , A = 3 .
B = 2( a + b + c ) .
And, C = ( ab + bc + ca ) .
•°• Discriminant ( D ) = b² - 4ac .
= [ 2( a + b + c )]² - 4 × 3 × ( ab + bc + ca ) .
= 4( a + b + c )² - 12( ab + bc + ca ) .
= 4[ ( a + b + c )² - 3( ab + bc + ca ) ] .
= 4( a² + b² + c² + 2ab + 2bc + 2ca - 3ab - 3bc - 3ca ) .
= 4( a² + b² + c² - ab - bc - ca ) .
= 2( 2a² + 2b² + 2c² - 2ab - 2bc - 2ca ) .
= 2[ ( a - b )² + ( b - c )² + ( c - a )² ] ≥ 0 .
[ °•° ( a - b )² ≥ 0, ( b - c )² ≥ 0 and ( c - a )² ≥ 0 ] .
This shows that both the roots of the given equation are real .
For equal roots, we must have : D = 0 .
Now, D = 0 .
⟹ ( a - b )² + ( b - c )² + ( c - a )² = 0 .
⟹ ( a - b ) = 0, ( b - c ) = 0 and ( c - a ) = 0 .
Hence, the roots are equal only when a = b = c . .
Solution:
We know that:
Root of quadratic equation,
(x-a)(x-b)+(x-b)(x-c)+(x-a)(x-c) = 0 are equal.
That means:
Now:
x² - (a + b)x + ab + x² - (b + c)x + bc + x² - (c + a)x + ca
3x² - 2(a + b + c)x + (ab + bc + ca)
And:
D = {2(a + b + c)}² - 4(ab + bc + ca).3 = 0
4{a² + b² + c² + 2(ab + bc + ca)} -12(ab + bc + ca) = 0
a² + b² + c² - ab - bc - ca = 0
2a² + 2b² + 2c² - 2ab - 2bc - 2ca = 0
(a - b)² + (b - c)² + (c - a)² = 0
This is possible only when,
Hence proved,
If roots of given equation are equal then: